Self‐Assembled Supramolecular Materials for Substrate Transport by External Stimuli - Xue Li; Yuichiro Kobayashi; Akira Harada; Hiroyasu Yamaguchi (Macromolecular Materials and Engineering)
Abstract Substrate transport within biological tissues is diverse, with the most fundamental process being transport across cell membranes, which plays a crucial role in sustaining life. In this study, an artificial substrate transport system based on hydrogels by utilizing molecular recognition and stimuli‐responsive substrates is developed. α‐ and β‐Cyclodextrins are selected as host molecules, while adamantane serves as the guest molecule, enabling the adhesion of two hydrogels through self‐assembly. Under light stimulation, the light‐responsive dye, azobenzene derivative, is transported between the two hydrogels. This research provides new insights into the development of light‐controlled substance transport systems, which can be applied to biological substance delivery and the creation of smart materials.